2014
DOI: 10.1016/j.cellsig.2014.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Disordered hepcidin–ferroportin signaling promotes breast cancer growth

Abstract: Iron homeostasis is strictly governed in mammals; however, disordered iron metabolism (such as excess iron burden) is recognized as a risk factor for various types of diseases including cancers. Burgeoning evidence indicates that the central signaling of iron homeostasis, the hepcidin-ferroportin axis, is misregulated in cancers. Nonetheless, the mechanisms of misregulated expression of iron-related genes along this signaling in cancers remain largely unknown. In the current study, we found increased levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
136
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 109 publications
(147 citation statements)
references
References 71 publications
7
136
0
Order By: Relevance
“…FPN plays a crucial role in maintaining the concerted iron homeostasis through controlling iron egress, and dysregulation of FPN would give rise to disordered iron metabolism, [10] likely resulting in FPN diseases, such as hereditary hemochromatosis and β-thalassemia [5]. Additionally, we also recently found reduced level of FPN in breast cancers, associated with poor prognosis in breast cancer patients [11,30]. To keep the balance of systemic iron metabolism, FPN is predominantly regulated by hepcidin through binding and inducing ubiquitin-dependent proteasomal degradation of FPN protein [6].…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…FPN plays a crucial role in maintaining the concerted iron homeostasis through controlling iron egress, and dysregulation of FPN would give rise to disordered iron metabolism, [10] likely resulting in FPN diseases, such as hereditary hemochromatosis and β-thalassemia [5]. Additionally, we also recently found reduced level of FPN in breast cancers, associated with poor prognosis in breast cancer patients [11,30]. To keep the balance of systemic iron metabolism, FPN is predominantly regulated by hepcidin through binding and inducing ubiquitin-dependent proteasomal degradation of FPN protein [6].…”
Section: Discussionmentioning
confidence: 70%
“…This study provides additional explanation for body iron changes in women upon estrogen alterations, such as a dramatic decline in the estrogen level in postmenopausal women. Since increased serum iron and tissue iron retention were observed in postmenopausal women, [30,66] excess iron would likely incur in detrimental effects on health. Therefore, in addition to its pronounced role in ameliorating menopausal symptoms, administration of a proper dose of estrogen (namely estrogen replacement therapy) might help to orchestrate systemic iron homeostasis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hepcidin induction in this cancer requires BMP2, another BMP/SMAD pathway ligand, and the inflammatory cytokine . Furthermore, recent work demonstrated that hepcidin is elevated in breast cancer patients and that diminished tumor expression of ferroportin promotes breast cancer growth (86,87). Finally, patients with the most advanced cancers have the lowest RBC hemoglobin concentration, and hemoglobin measurements are conversely correlated with inflammatory markers and hepcidin (88).…”
Section: Other Causes Of the Anemia Of Inflammationmentioning
confidence: 99%
“…The molecular basis of hepcidin function is to induce iron exporter ferroportin internalization and degradation within lysosomes through an ubiquitin-dependent manner, by which iron efflux out of macrophages and intestinal absorption would be inhibited [9,10]. Hepcidin expression is promoted by excess iron and inflammation, and is reversely suppressed by erythropoiesis and hypoxia [6,[9][10][11][12]. These different ways in the regulation of hepcidin concertedly limit intestinal iron absorption during iron overload, and increase iron availability during erythropoiesis, e.g.…”
Section: Introductionmentioning
confidence: 99%